Purwarupa Sistem Pendataan Pengunjung dan Pengendalian Perangkat Laboratorium Dalam Pengembangan Smart Campus - Alfa Satyaputra; Arnold Aribowo; Heny Ispur Pratiwi (Ikatan Ahli Informatika Indonesia (IAII), 2017)
The laboratory visitors data collection system serves as a timestamp data collection of laboratory visitors, and the control system is set for controlling electrical devices such as air conditioners, lights, and door locks inside the laboratory room according to the visitors amount, both are integrated as one system for implementing the development of Smart Campus and supporting conveniences and security for Lecturers, staff and students. The system uses hardware such as door lock solenoid, relay board, RFID reader, serial-cables and Arduino microcontrollers. Some software are used such as Node.js scripts (JavaScript runtime environment) as the central logic and communication, one Arduino microcontroller programmed with Arduino software program, and another Arduino microcontroller is embedded with firmware Firmata and application software such as server XAMPP for web pages using Bootstrap framework and Javascript library such as AngularJS, JQuery and Javascript Bootstrap. Furthermore, MySQL is used as a database by using a serial protocol, and then WebSocket and Johnny-Five Framework are used as a complement system solution. Overall integration of the systems is expected to run smoothly as designed.